Polymer composites Volume 1 - Thomas, Sabu. (Weinheim : Wiley-VCH, 2012)
The first systematic reference on the topic with an emphasis on the characteristics and dimension of the reinforcement. This first of three volumes, authored by leading researchers in the field from academia, government, industry, as well as private research institutions around the globe, focuses on macro and micro composites. Clearly divided into three sections, the first offers an introduction to polymer composites, discussing the state of the art, new challenges, and opportunities of various polymer composite systems, as well as preparation and manufacturing techniques. The second part.
2.5.3.1 Self Consistent Method for the Determination of Dynamic Shear Yield Strength2.5.3.2 Calculation of Initial Hugoniot Shocked State and Hugoniot Stress-Strain Curve; 2.5.3.3 Calculation of Off-Hugoniot States for Reshock-Release Loading; 2.5.3.4 Determination of the Critical Shear Strength in the Shocked State for S2-Glass GRP; 2.6 Summary; References; 3 Interfaces in Macro- and Microcomposites; 3.1 Introduction; 3.2 Characterization of Interfaces in Macro- and Microcomposites; 3.2.1 Surface Treatments of Reinforcements for Composite Materials; 3.2.2 Microscale Tests.
Includes bibliographical references and index.
Keywords: Polymeric composites; Polymers; TECHNOLOGY & ENGINEERING -- Material Science; Polymeric composites; Polymers; Electronic books